2007
DOI: 10.1152/jn.00747.2006
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity in the Responses of Adjacent Neurons to Natural Stimuli in Cat Striate Cortex

Abstract: When presented with simple stimuli like bars and gratings, adjacent neurons in striate cortex exhibit shared selectivity for multiple stimulus dimensions, such as orientation, direction, and spatial frequency. This has led to the idea that local averaging of neuronal responses provides a more reliable representation of stimulus properties. However, when stimulated with complex, time-varying natural scenes (i.e., movies), striate neurons exhibit highly sparse responses. This raises the question of how much resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
59
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(72 citation statements)
references
References 66 publications
(59 reference statements)
13
59
0
Order By: Relevance
“…We still have an incomplete understanding of the magnitudes of typical correlation coefficients between neural responses, especially when the systems are studied with natural stimuli [38]. There have been many studies, particularly in various cortical areas of the visual system (e.g.…”
Section: (C) Correlations In Neural Signalsmentioning
confidence: 99%
“…We still have an incomplete understanding of the magnitudes of typical correlation coefficients between neural responses, especially when the systems are studied with natural stimuli [38]. There have been many studies, particularly in various cortical areas of the visual system (e.g.…”
Section: (C) Correlations In Neural Signalsmentioning
confidence: 99%
“…Characteristics of receptive field dynamics (DeAngelis et al 1993;Malone et al 2007;Ringach et al 1997) are also affected by the reported findings, especially when considering the evolution of frequency selectivity (Malone et al 2007). Additionally, observed heterogeneity and distribution of receptive field sizes and types (Gawne et al 1996;Maldonado and Gray 1996;Yen et al 2007) may be even larger than reported.…”
Section: Discussionmentioning
confidence: 59%
“…91-3207 (National Institutes of Heath, Bethesda, MD, 1991). A detailed description of the surgical and recording techniques can be found in Yen et al (2007).…”
Section: Surgery and Recordingsmentioning
confidence: 99%
“…The dominance of inhibitory influences in the population is usually interpreted as an effect of the retinotopic surround (Angelucci et al 2002), but could equally well be explained from the more general principle of sparseness of neuronal coding. With natural stimulation, activity in neighbouring neurons becomes decorrelated and more specialized (Vinje and Gallant 2000;Yen et al 2007). As stimulus complexity increases, therefore, a majority of neurons will receive net-inhibition, while a minority will receive net-excitation.…”
Section: Contextual Modulation In V1mentioning
confidence: 99%
“…In this paper we focus on the spatial organization of contextual modulation under wide-field stimulation. This means that we will only briefly touch on a number of other relevant phenomena, including the increased sparseness of the neuronal code in the presence of visual context beyond the RF (Vinje and Gallant 2000;Yen et al 2007), the effect of visual working memory on the modulation of neural responses (Super et al 2001;Harrison and Tong 2009), and the influence of contextual stimuli on response latency profiles (Kapadia et al 1999;Li et al 2000;Huang and Paradiso 2005). In the section ''Mechanisms of horizontal integration into V1'', however, we will discuss in some detail the relevance of spatiotemporal dynamics of V1, as well as motion in the visual field induced by saccadic activity.…”
Section: Contextual Modulation In V1mentioning
confidence: 99%